(untitled) (Revista Argentina de Cirugía, 2021)
An adult, female patient was admitted with diagnosis of digestive bleeding and hemodynamic instability. Colonoscopy showed bleeding from the appendicular ostium. An appendectomy was performed, with resolution of the digestive hemorrhage and good postoperative outcome. Pathology showed angiodysplasia of the cecal appendix. A bibliographical revision is done with considerations on the frequency, diagnostic workup and alternative therapies.